Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dan Likuiditas Terhadap Nilai Perusahaan - Lucia Evalina Kristianti, Jonnardi (Jurnal Paradigma Akuntansi, 2022)
This research aims to obtain empirical evidence regarding the effect of profitability, leverage, company size, and liquidity on firm value in basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample was selected using purposive sampling method and the valid data were 58 companies. The data processing technique uses multiple regression analysis assisted by the Eviews 11.0 program and Microsoft Excel 2013. The results of this study indicate that the four independent variables have a significant effect on firm value, namely profitability, leverage, company size and liquidity, The implication of this research is the need to increase profitability, leverage, company size and liquidity to increase firm value which will provide positive signals for investors.